HYDROCARBON DISTRIBUTION ANALYSIS OF RESERVOIR B, C, D LOWER SIHAPAS FORMATION IN KIREI WB FIELD, CENTRAL SUMATRA BASIN - A. BEHAKI, WAWAN
Kirei WB field was discovered in 1985 which started production in 1988 . Peak production of 25,339 BOPD, accumulated up to March 2013 about 43 MMbbl . Estimation of remaining reserves is approximately about 10MMbbl, Therefore this production field is still believed to be potential to develop. There were several development wells drilled in this field are considered to not succeed. Knowing that these new wells are within drainage radius of existing wells, and also due to reservoir compartmentalization. Primary data of this study are conventional cores (3 wells), well logs (37 wells) and 3D seismic data. Secondary data are petrophysical analysis, biostratigraphy and reservoir properties information such as original and current OWC (oil water contact), and pressure data (MDT). In aim to define geometry and reservoir characters, lithofacies analysis and interpretation of facies associations based on well logs data and cores should be conducted, by using the concept of sequence stratigraphy, the chrono correlation of each wells have been done. Each reservoir unit determine by using the chrono-correlation and integrated with petrophysical rock properties. Depositional facies maps are define from net sand calculation and from seismic attribute extraction which lead to geological interpretation especially facies association. The analysis of stratigraphic compartmentalization has been done by analyzing the geometry of the reservoir, OWC review from depth structure map and electrofacies character analysis. This multidisciplinary study are expected to yield a very less uncertainty reservoir model, and lead to successful development infill drilling. The result of this study point out that WB Kirei field is not compartmentalized structurally (cause by fault), Based on depth structure map of its reservoir, isopach net sand by following the trend of seismic attributes and electrofacies character, chrono-correlation between wells, there are also no occurrence of compartmentalization. The differences of hydrocarbon accumulation is possible due to the existence of a permeability barrier which is believed to distinct one reservoir body unit to another unit. Matter of this study is hydrodynamic concepts can not be held in this field considering to oil-water contact position that has similar relative depth.